Photovoltaic (PV) thermal performance simulation using segmentation lapping fin passive cooling - Ahmad Yonanda; Amrizal Amrizal; Harmen Harmen; Ahmad Riszal; Fauzi Ibrahim (Politeknik Negeri Lhokseumawe, 2022)
The sun is a renewable energy source that has several advantages such as being easy to obtain, free of pollution, and available in sufficient quantities. The heat energy received by the photovoltaic can cause an increase in surface temperature, resulting in a decrease in electrical efficiency. One of the efforts to increase photovoltaic electrical efficiency is using air cooling, by adding absorber fins or thermal photovoltaic (PV/T). The lapping type fin has superior performance in reducing the temperature of the PV module compared to the linear (conventional) fin type. The purpose of this study was to compare the performance of thermal PV using conventional fins with lapping segmentation fins carried out using the CFD approach using ANSYS Fluent. The simulation test procedures include: making linear fin geometry (conventional), linear lapping and segmentation lapping, conducting mesh quality studies, and determining boundary conditions and modeling parameters. Modeling variations in the direction of airflow 0°, 15°, 30°, 45°, 60°, 75°, and 90°. The numerical simulation results show that the use of segmented lapping fins can reduce the PV surface temperature by 1.79 °C or about 4.11% compared to conventional (linear) lapping in the airflow direction of 90º (parallel to the fins). The results of this study support the use of integrated PV and passive cooling systems to reduce efficiency losses in actual conditions, where there is a multidirectional airflow characteristic, which may not be advantageous for conventional heatsinks.